The Role of Artificial Intelligence Literacy in Building the Digital Competence Of 21st Century Teacher Candidates - Hikmah, Nurul; Maryam, Maryam (Jujurnal Publisher, 2024)
The rapid advancement of Artificial Intelligence (AI) has transformed educational practices and increased the demand for prospective teachers with digital competencies and AI literacy. However, research examining the role of AI literacy in strengthening prospective teachers' digital competencies is still limited. This study aims to analyze the role of Artificial Intelligence literacy in developing the digital competencies of 21st-century pre-service teachers. A qualitative approach using library research methods was adopted, following the principles of a systematic literature review. Relevant studies published between 2020 and 2026 were identified from Scopus, Web of Science, ScienceDirect, SpringerLink, Taylor & Francis, Emerald Insight, Wiley Online Library, IEEE Xplore, and Google Scholar. Literature selection followed the PRISMA framework, while data were analyzed using content analysis and thematic synthesis. The findings revealed that AI literacy serves as a foundational competency encompassing conceptual knowledge of AI, application skills, critical evaluation, ethical awareness, data security, and pedagogical integration. These dimensions strengthen critical thinking, digital creativity, computational thinking, problem-solving, and data-driven decision-making, ultimately enhancing digital competencies in information literacy, communication, content creation, digital security, adaptive pedagogy, and ethical AI integration. This study concludes that integrating AI literacy into teacher education curricula is crucial for preparing future teachers to respond effectively, responsibly, and innovatively to the digital transformation of education.